ANALYSIS OF PUBLIC TRANSPORT DEVELOPMENT IN METROPOLITAN CITY BASED ON ORIGIN-DESTINATION (CASE STUDY: METRO CAPSUL BANDUNG) - Triyadani, Ade; Santoso, Idwan; Wibowo, Sony Sulaksono (FAKULTAS TEKNNIK UNIVERSITAS SWADAYA GUNUNG JATI, 2020)
Development of new mode of metro kapsul as mass transportation mode in Bandung with corridor plan from Station Hall to Tegallega and return to Station Hall with plan of 19 stop station which can give contribution to congestion problem and lack of public transportation service in Bandung city. This study aims to analyze the potential of demand with the data of origin - destination of the respondent in the corridor plan of the metro capsule in order to give a description of the movement in the origin-destination matrix, in analysis for potential demand used the modal movement assumption of private vehicles, public transport and pedestrian, The location of priority shelter at the beginning of development by using multicriteria analysis while for operational analysis is calculated some variables of capsule metro operating system (headways, frequencies, etc). The result of origin-destination matrix analysis is getting potential demand of metro capsule during weekdays on-peak of 3529 pass/hour, off-peak of 2116 pass/hour. The result of location priority stop location will get 6 (six) stop location recommended in ?Stasiun Bandung, Pasar Baru, Pasar Anyar, Taman Tegallega, ITC Kebon Kelapa and Alun-Alun Bandung?. From the operational results of metro capsule, obtained frequence of 20 Unit/jam, headways 3 minutes, the number of vehicles required 8 vehicles, on weekdays and weekends when on-peak and off-peak.